Experiential Learning as Archival Activation: Reflections on University of Calgary’s Student Archival Residency Project Phase One - Jones, David; Reed, Lelland; Reid, Laura; Iles, Shea (CAML Review / Revue de l'ACBM, 2025)
Music archives hold unique value in understanding the process of creators and sparking creativity in new researchers through their exploration. The University of Calgary Archives and Special Collections preserves and shares the archives of prominent composers, record labels, musicians, and music historians. In 2024, three colleagues from University of Calgary Libraries and Cultural Resources were awarded funding from the Taylor Institute for Teaching and Learning to initiate an archives student-in-residence program. Through purposeful connection with archives, students, archivists and librarians, the project’s goal is to investigate the use of the archive as a site for experiential education. This student-in-residence program invites three students over the course of three years to critically explore, analyze, synthesize, interpret, and activate three prominent music archival fonds: Norma Beecroft, Edith Fowke, and Melvin Crump. The principal investigators will work with the student residents through a process of co-inquiry to support them through the archival research process and applying creative approaches to the rich and varied archival materials maintained by Archives and Special Collections. Through multiple iterations of residencies, one every year over the course of three years, team leads will be able to move beyond a single context and look for patterns that emerge from the collected experiences. This article explores and reflects on the first year of the project focused on the Norma Beecroft fonds and explores the goals of the long-term project into the coming years.